Host cell targeting of novel antimycobacterial 4-aminosalicylic acid derivatives with tuftsin carrier peptides - Borbála Horváth, Lilla; Krátký, Martin; Pflégr, Václav; Méhes, Előd; Gyulai, Gergő; Kohut, Gergely; Babiczky, Ákos; Biri-Kovács, Beáta; Baranyai, Zsuzsa; Vinšová, Jarmila; Bősze, Szilvia (European journal of pharmaceutics and biopharmaceutics, 2022)
Mycobacterium tuberculosis is an intracellular pathogen and the uptake of the antimycobacterial compounds by host cells is limited. Novel antimycobacterials effective against intracellular bacteria are needed. New N-substituted derivatives of 4-aminosalicylic acid have been designed and evaluated. To achieve intracellular efficacy and selectivity, these compounds were conjugated to tuftsin peptides via oxime or amide bonds. These delivery peptides can target tuftsin- and neuropilin receptor-bearing cells, such as macrophages and various other cells of lung origin. We have demonstrated that the in vitro antimycobacterial activity of the 4-aminosalicylic derivatives against M. tuberculosis H37Rv was preserved in the peptide conjugates. The free drugs were ineffective on infected cells, but the conjugates were active against the intracellular bacteria and have the selectivity on various types of host cells. The intracellular distribution of the carrier peptides was assessed, and the peptides internalize and display mainly in the cytosol in a concentration-dependent manner. The penetration ability of the most promising carrier peptide OT5 was evaluated using Transwell-inserts and spheroids. The pentapeptide exhibited time- and concentration-dependent penetration across the non-contact monolayers. Also, the pentapeptide has a fair penetration rate towards the center of spheroids formed of EBC-1 cells.
Keywords: N-substituted 4-aminosalicylic acid derivatives; kyselina aminosalicylová; Excipients; antibakteriální látky; Peptides; pomocné látky; tuftsin; Antitubercular Agents; antituberkulotika; Microbial Sensitivity Tests; Tuftsin; mikrobiální testy citlivosti; Mycobacterium tuberculosis; Tuftsin carrier peptides; Host cell targeted delivery; Anti-Bacterial Agents; Aminosalicylic Acid; peptidy; Neuropilin receptor; Antimycobacterial compound